Efficacy of Arruda Algorithm for Localization of Accessory Pathway in Patients with Wolff-Parkinson-White Syndrome from The Surface ECG - Bista, Anupam; Rajbhandari, Sujeeb; Maskey, Arun; Ghimire, NIrmal; Bhatta, Ajay; Acharya, Den Prasad; Rajthala, Prabesh; Gurung, Kalpana (Journal of National Heart and Lung Society Nepal, 2024)
Background: In Wolff-Parkinson-White (WPW) syndrome, Accessory pathway can be localized from surface Electrocardiogram (ECG) using different algorithm. Arruda algorithm is established and clinically tested localization method which uses initial 20 milliseconds of preexcitation in 5 leads (I, II, III, aVF and V1) of standard 12 lead ECG. Methods: A hospital based observational study was conducted in 54 patients with WPW syndrome from April, 2023 to January, 2024 in Shahid Gangalal National Heart Centre. Data on demographics, clinical features, ECG localization using Arruda algorithm and Electrophysiological localizations of accessory pathway were collected through structured proforma and predictive accuracy of Arruda algorithm was determined. Statistical analysis was done using the SPSS version 16 software. Results: The mean age of patients was 36.39±13.99 years, with maximum number of patients from 20-45 years of age group. 57.4% were male and the most common pathway being left lateral/ anterolateral. Arruda algorithm accurately localized accessory pathway in 90.7% (n=49) of patients. The overall sensitivity and specificity of the Arruda algorithm to exactly localize accessory pathway in WPW syndrome was 88.1% and 98.7% respectively.Conclusion: Arruda algorithm is sensitive and specific to localize accessory pathway in patients with WPW syndrome undergoing electrophysiological study and radiofrequency ablation.